(3GdeTJQcGJs - (3GdcGXej, eMeO Cejf Hf eMeO Ydj, (B1068 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B.. (3Efj deG fXQJ aj cJGH GdeSei HLGeY GdebGd ajeG jJYdb HCMhGd GdCMGOjK hGdQLGd GdPj gh ef eDdaGJ TjNfG (B.. (3ahLOJ aj GdHGH GdKGdK YTQ CZdGWG cKjQI dG JNai Ydi ef dg COfi HUjQI hTGY Hjf GdWdHI aJbQHJ Edi Gdg HEUdGM eG ajg ef GdZdW GdhGVM (B... (3GYJeGOs
(3BNQgG (B:s
... (3ceG Mce GdYdGeI (B.. (3HUMI WQjb GdUOhb Edi ESeGYjd Hf QHGM hWQjb GdMSjf Hf jRjO hWQjb GdMGQK Hf (B... (3hgPG eG CQOfG EjQGOg ef GdCdaGX GdJj jbY ajgG GdGdJHGS Ydi cKjQ ef GdfGS hajg GdcaGjIs
(3JHUQI GdYfhGf (B:s
(3JYdjbGJ hEUdGM CZGdjW (B- (3gh ZjQ TQMg , hjSei (B: (3gOGjI GdeMOKjf Edi WQjbI GdeMeOjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 \ 41s
(3GdPQjYI (B21 \ 3858s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs